# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \sqrt {x -y}
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = t y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t}{y^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{t -2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-4 y = t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = {\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = t \,{\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+3 y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x^{2}-y}-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+y}{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (y\right )-\cos \left (x \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 1-\cot \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (3 x -y\right )^{{1}/{3}}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }+x y = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{2}-y+\frac {3}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y-1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y-1\right ) x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+2 x -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+y}{x -1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y}{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x -y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y-2 x^{2}-3
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x -y
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+\left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }-y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{2} = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x \sqrt {1+y^{2}}+y y^{\prime } \sqrt {x^{2}+1} = 0
\] |
✓ |
✓ |
|
\[
{}x \sqrt {1-y^{2}}+y \sqrt {-x^{2}+1}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{-y} y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y \ln \left (y\right )+x y^{\prime } = 1
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = a^{x +y}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y} \left (x^{2}+1\right ) y^{\prime }-2 x \left (1+{\mathrm e}^{y}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x \sqrt {1-y^{2}} = \left (x^{2}+1\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )^{3}+\left (1+{\mathrm e}^{2 x}\right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} \sin \left (x \right )+\cos \left (x \right )^{2} \ln \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a x +b y+c
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = a \left (x y+1\right )
\] |
✓ |
✓ |
|
\[
{}a^{2}+y^{2}+2 x \sqrt {a x -x^{2}}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } \cos \left (y\right )+1 = 0
\] |
✗ |
✓ |
|
\[
{}x^{2} y^{\prime }+\cos \left (2 y\right ) = 1
\] |
✗ |
✓ |
|
\[
{}x^{3} y^{\prime }-\sin \left (y\right ) = 1
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }-\frac {\cos \left (2 y\right )^{2}}{2} = 0
\] |
✗ |
✓ |
|
\[
{}{\mathrm e}^{y} = {\mathrm e}^{4 y} y^{\prime }+1
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime } = y-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x \left (\pi +y\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+\sin \left (2 y\right ) = 1
\] |
✗ |
✓ |
|
\[
{}x y^{\prime } = y+x \cos \left (\frac {y}{x}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x -y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y \left (\ln \left (y\right )-\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}-x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+\sqrt {y^{2}-x^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}4 x -3 y+\left (2 y-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-x +\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y-2+\left (1-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y-7 x +7-\left (3 x -7 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y-2+\left (x -y+4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+\left (x -y-2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +3 y-5+\left (3 x +2 y-5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}8 x +4 y+1+\left (4 x +2 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -2 y-1+\left (3 x -6 y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+\left (x +y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } \left (x -y^{2}\right )+y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{6}+x^{3} = 6 x y^{5} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \left (1+\sqrt {x^{2} y^{4}+1}\right )+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y^{3}+3 \left (y^{3}-x \right ) y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}x^{2}-x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 2 x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = {\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \cos \left (x \right )-y \sin \left (x \right ) = 2 x
\] |
✓ |
✓ |
|